Association of markers of inflammation on attention and neurobehavioral outcomes in survivors of childhood acute lymphoblastic leukemia - Cheung, Yin Ting; To, Kenneth Kin-Wah; Hua, Rong; Lee, Chui Ping; Chan, Agnes Sui-Ying; Li, Chi Kong (Frontiers in Oncology, 2023)
Background: Survivors of childhood acute lymphoblastic leukemia (ALL) are at-risk of developing cognitive impairment and neurobehavioral symptoms. Inflammation induced by a compromised health status during cancer survivorship is proposed as a pathophysiological mechanism underlying cognitive impairment in cancer survivors. Objectives: To evaluate the associations of biomarkers of inflammation with attention and neurobehavioral outcomes in survivors of childhood ALL, and to identify clinical factors associated with biomarkers of inflammation in this cohort. Methods: We recruited patients who were diagnosed with ALL at ≤ 18 years old and were currently ≥5 years post-cancer diagnosis. The study outcomes were attention (Conners Continuous Performance Test) and self-reported behavioral symptoms (Adult Self-Report [ASR] checklist). Using a commercial screening kit, survivors’ plasma (5ml) was assayed for 17 cytokines/chemokine cell-signaling molecules that are associated with neurodegenerative diseases. The final panel of the targeted markers included interleukin (IL)-8, IL-13, interferon-gamma (IFN-γ), monocyte chemoattractant protein-1 (MCP-1), macrophage inflammatory protein-1β, and tumor necrosis factor-α. Biomarker levels were rank-ordered into tertiles based on the sample distribution. Multivariable general linear modeling was used to test for associations between biomarkers and study outcomes in the overall cohort and stratified by gender. Results: This study included 102 survivors (55.9% males, mean[SD] age 26.2[5.9] years; 19.3[7.1] years post-diagnosis). Survivors within top tertiles of IFN-γ (Estimate =6.74, SE=2.26; P=0.0037) and IL-13 (Estimate =5.10, SE=2.27; P=0.027) demonstrated more inattentiveness. Adjusting for age, gender and treatment, more self-reported thought (Estimate=3.53, SE=1.78; P=0.050) and internalizing problems (Estimate =6.52, SE=2.91; P=0.027) correlated with higher IL-8. Higher levels of IL-13 (RR = 4.58, 95% CI: 1.01–11.10) and TNF-α (RR = 1.44, 95% CI: 1.03–4.07) were observed in survivors had developed chronic health conditions (n=26, 25.5%). The stratified analysis showed that association of IFN-γ with attention was stronger in male survivors than in female survivors. Conclusion: Inflammation due to cancer-related late effects may potentially be mechanistic mediators of neurobehavioral problems in pediatric ALL survivors. Markers of inflammation can potentially be applied to assess or monitor the effectiveness of interventions, particularly behavioral interventions, in improving cognitive outcomes in survivors. Future work includes understanding the underlying gender-specific pathophysiology behind functional outcomes in the population.